TINJAUAN YURIDIS TERHADAP FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA SEBELUM DAN SESUDAH PERUBAHAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA 1945 - Priadi, Yan Agus; Haryono, Dodi; ', Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Undang-Undang Dasar 1945 are the highest law in nations and country which Undang-Undang Dasar 1945 regulated the relationship between goverment to the country and relationship between the civilizated organization, in order to Undang-Undang Dasar 1945 can called as constitution of Republic of Indonesian. Its changes the strength of president after government stated out the law of Majelis Permusyawaratan Rakyat (MPR), are Provisionals MPR Decree No. VIII/MPR/1998 was removed Provisional MPR Decree No. IV/MPR/1983. Its dialed that Provisional MPR Decree about the Referendum, its mean nothing the problem for MPR did the reformation to UUD 1945. As the consequennce from the strength of President as the central power. ( Executive heavy).The kind of this research is used the comperative law and history law. The Study can also called as the library research because this study only based on to scunder material like material of libraries as the primary material, although in this study the writer reviewed the function of legislation of DPR RI before and after Amendments Undang-Undang Dasar Republic of Indonesian 1945 (UUD 1945) then again comphared it to get the summarizing.The formulation of this sudy is what the background of the function changes of legislation that regulated in changes of UUD 1945, and How about the different function of legislation before and after amendments UUD 1945, And what the weakness and strengths function of legislation before and after amendments UUD 1945.The result of this study showed that the background of changes the function of legislation that regulated in changes UUD 1945 are with stated out Provisionals Majelis Permusyawaratan Rakyat(MPR) is Provisionals MPR No VIII/MPR/1998 its removed Provisionals MPR Decree No IV/MPR/1983. As the conscequence from the strength of president as central power (executive heavy). While the different is there are separation of power from president to DPR, to the strength mecanisme check and balances, there are addition in planning process of the legislation form which doing legislation national progam (Proglegnas) and increasing Academic texts in planning of the legislation form. Althought to be the strength and the weakness function of legislation before and after Amendments UUD 1945, the function of legislation is president. So regulation of legislations which as result suit to necessary of executive as actor of legislations while after amendments is return it the function of DPR. In additition to be the weakness is the formed UU time necessary longer than that nothing procedure more continue if “Dead Lock” in learning between president and DPR, its caused productifity of formed legislation is“somewhat barren”